1987
DOI: 10.1007/bf01852082
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic changes inT. cruzi-infected rats after the ajmaline test

Abstract: Fifty-eight chronically T. cruzi-infected rats and 26 control rats were submitted to the ajmaline test (1 mg/kg, i.v. during ECG monitoring) after obtaining the resting ECG. Abnormal ECG tracings were detected in the resting ECG of 26 (44%) infected rats. After ajmaline injection, a decrease in heart rate was observed in control but not in infected rats. P wave enlargement, lengthening of the QRS complex, and increase of the PR as well as the QaT intervals were detected in all animals. Ajmaline induced right a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1988
1988
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, since these methods cannot be applied to experimental animals, an experimental model for the indeterminate form of Chagas' disease that is simple enough for extensive use is still unavailable. When we used a single ECG lead [11] followed by a complete ECG study (9 leads) [12], we obtained about the same percentage in T. cruzi-infected rats. Our experiments were based on the findings by Chiale et al [13] that 30~ of patients with the indeterminate form of Chagas' disease present ECG abnormalities evoked by IV injection of ajmaline.…”
mentioning
confidence: 58%
See 4 more Smart Citations
“…However, since these methods cannot be applied to experimental animals, an experimental model for the indeterminate form of Chagas' disease that is simple enough for extensive use is still unavailable. When we used a single ECG lead [11] followed by a complete ECG study (9 leads) [12], we obtained about the same percentage in T. cruzi-infected rats. Our experiments were based on the findings by Chiale et al [13] that 30~ of patients with the indeterminate form of Chagas' disease present ECG abnormalities evoked by IV injection of ajmaline.…”
mentioning
confidence: 58%
“…We have previously conducted a study in which ajmaline provoked electrocardiographic changes (not observed in controls) thought to be representative oflatent Chagas' heart disease [12]. However, since we did not perform a simultaneous pathological study, these changes were only speculative.…”
Section: T Cruzi-infected Ratsmentioning
confidence: 96%
See 3 more Smart Citations